THE EFFECT OF SOCIAL MEDIA ADDICTION AND TIME MANAGEMENT ON THE LEARNING ACHIEVEMENT OF ECONOMICS EDUCATION STUDENTS: (Survey on Students of the Department of Economic Education, Siliwangi University Class of 2019) - Agustian, Kiki; Suherti, Heti; Nurdianti, Raden Roro Suci (Transpublika Publisher, 2023)
Excessive usage of social media can lead to distractions and reduced focus, especially when it interferes with dedicated study time. Constant notifications, scrolling through feeds, and engaging in online conversations can hinder effective studying and educational activities. This study aims to investigate the impact of social media addiction and time management on learning achievement. The research utilizes a quantitative survey method with an explanatory survey research design. The sampling technique employed is a saturated sample, encompassing the entire population as the research sample. Data collection is done through a questionnaire, and the data is analyzed using multiple linear regression analysis, including both partial and simultaneous tests. The results of the partial test indicate that social media addiction does not have a significant effect on learning achievement, with a significance value of 0.329, whereas time management has a significant effect on learning achievement, with a significance value of 0.000. The simultaneous test results demonstrate that both social media addiction and time management significantly influence learning achievement, with a significance value of 0.000. Consequently, this study concludes that social media addiction and time management significantly impact learning achievement, with a coefficient of determination of 64%.